Land for the Athenian Poor: The Politics of Redistribution Outside Attica During the Fifth Century BCE - Gallego, Julian (Pnyx: Journal of Classical Studies, 2024)
The main concern of this research is the distribution of land carried out by Athens outside Attica during the fifth century BCE, which mostly favoured poor Athenians according to the perspective held in this article. The basic assumption is that most of the colonists and cleruchs came from the Athenian lower classes, which encompassed all the thetes and the bulk of the zeugitai keeping in mind the Solonian census classes. It is argued that in the colonisation process there was a hoplite farm model that operated as a reference pattern for the Athenian state to distribute plots and/or to collect rents in favour of its citizens. In order to sustain this, it is first defined the situation of the zeugitai and the thetes during the sixth and fifth centuries; secondly, it is presented some rough figures of the total male citizen population and of the number of Athenian hoplites, to imagine the possible number of citizens available to emigrate; thirdly, it is analysed three situations that show, in one way or another, the validity of the hoplite farm model for land allocations in Athenian settlements and the beneficiaries of this founding policy: the colony of Brea, the cleruchy on Lesbos, and the colony of Melos; finally, it is proposed some concluding remarks about the Athenian land distribution policy that favoured the lower classes.